A subset of N-substituted phenothiazines inhibits NADPH oxidases - Seredenina, Tamara; Chiriano, Gianpaolo; Filippova, Aleksandra; Nayernia, Zeynab; Mahiout, Zahia; Fioraso-Cartier, Laetitia; Plastre, Olivier; Scapozza, Leonardo; Krause, Karl-Heinz; Jaquet, Vincent (Free radical biology & medicine, 2015)
NADPH oxidases (NOXs) constitute a family of enzymes generating reactive oxygen species (ROS) and are increasingly recognized as interesting drug targets. Here we investigated the effects of 10 phenothiazine compounds on NOX activity using an extensive panel of assays to measure production of ROS (Amplex red, WST-1, MCLA) and oxygen consumption. Striking differences between highly similar phenothiazines were observed. Two phenothiazines without N-substitution, including ML171, did not inhibit NOX enzymes, but showed assay interference. Introduction of an aliphatic amine chain on the N atom of the phenothiazine B ring (promazine) conferred inhibitory activity toward NOX2, NOX4, and NOX5 but not NOX1 and NOX3. Addition of an electron-attracting substituent in position 2 of the C ring extended the inhibitory activity to NOX1 and NOX3, with thioridazine being the most potent inhibitor. In contrast, the presence of a methylsulfoxide group at the same position (mesoridazine) entirely abolished NOX-inhibitory activity. A cell-free NOX2 assay suggested that inhibition by N-substituted phenothiazines was not due to competition with NADPH. A functional implication of NOX-inhibitory activity of thioridazine was demonstrated by its ability to block redox-dependent myofibroblast differentiation. Our results demonstrate that NOX-inhibitory activity is not a common feature of all antipsychotic phenothiazines and that substitution on the B-ring nitrogen is crucial for the activity, whereas that on the second position of the C ring modulates it. Our findings contribute to a better understanding of NOX pharmacology and might pave the path to discovery of more potent and selective NOX inhibitors. [Display omitted] •A subset of N-substituted phenothiazines inhibits NOX enzymes.•Thioridazine is the most potent N-substituted phenothiazine.•Thioridazine mitigates differentiation of human fibroblasts into myofibroblasts.•N-substituted phenothiazines represent a scaffold for designing new NOX inhibitors.